(untitled) (World Bulletin of Social Sciences, 2022)
John Updike, is One of America’s avant-garde novelists, and one of several who has fictionalized the aftermath of 9/11. Terrorist has depicted the Muslim other in the post-9/11 geopolitical setting of conflicts in Iraq, Afghanistan, and Palestine by using a Muslim American adolescent as the main character. This research aims to address terrorists’ exemplifications of these Muslim countries’ geography and place them in post-9/11 geopolitical and colonial contexts. Colonial shadows are inferences and insinuations that justify, legitimize, and legitimize colonial activities and conditions, either through the narrative’s image of Muslims or by displaying relevant geography. This study tries to comprehend and explicate the overt and covert colonial connotations and correlations between the narrative and colonized topographies by demonstrating the story’s colonial shadows. Terrorist depicts Palestinians as being associated with violence and terrorism in comparison to nonviolent Israelis in order to justify Israel’s colonial status in Palestine. Furthermore, the American colonial wars in Iraq and Afghanistan are portrayed as benign and reasonable actions of self-defense